LC-HR-MS/MS standard urine screening approach: pros and cons of automated on-line extraction by turbulent flow chromatography versus dilute-and-shoot and comparison with established urine precipitation - Helfer, Andreas Günter; Meyer, Markus Robert (Journal of chromatography, 2017)
Comprehensive urine screening for drugs and metabolites by LC-HR-MS/MS using Orbitrap technology has been described with precipitation as simple workup. In order to fasten, automate, and/or simplify the workup, on-line extraction by turbulent flow chromatography and a dilute-and-shoot approach were developed and compared. After chromatographic separation within 10min, the Q-Exactive mass spectrometer was run in full scan mode with positive/negative switching and subsequent data dependent acquisition mode. The workup approaches were validated concerning selectivity, recovery, matrix effects, process efficiency, and limits of identification and detection for typical drug representatives and metabolites. The total workup time for on-line extraction was 6min, for the dilution approach 3min. For comparison, the established urine precipitation and evaporation lasted 10min. The validation results were acceptable. The limits for on-line extraction were comparable with those described for precipitation, but lower than for dilution. Thanks to the high sensitivity of the LC-HR-MS/MS system, all three workup approaches were sufficient for comprehensive urine screening and allowed fast, reliable, and reproducible detection of cardiovascular drugs, drugs of abuse, and other CNS acting drugs after common doses.
Published online: 21 June 2016
Gesehen am 23.04.2018